2020
DOI: 10.17265/2161-6264/2020.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice AUXIN BINDING PROTEIN57 (OsABP57) Overexpression in Response to Flooding

Abstract: This study reports the effects of Oryza sativa AUXIN BINDING PROTEIN57 (OsABP57) overexpression towards flooding in rice. OsABP57 was previously reported to activate plasma membrane H + -ATPase. Earlier studies address the ability of transgenic OsABP57 overexpression in enduring drought and salinity stresses but none on the flooding. In this study, complete submergence analysis was carried out and several morphophysiological parameters were analyzed such as plant height, root architecture and relative chloroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Image J allows the measurement of density profiles, peak heights as well and peak intensity of the band of the expected molecular weight. Gene expression is relative to the loading control gene from the control plant (without treatment) and normalized to the internal constitutive gene (target gene × (loading gene (control)/internal constitutive gene)) (Zambrose et al, 2020). The fold change value was generated from the normalized value.…”
Section: Densitometry Analysismentioning
confidence: 99%
“…Image J allows the measurement of density profiles, peak heights as well and peak intensity of the band of the expected molecular weight. Gene expression is relative to the loading control gene from the control plant (without treatment) and normalized to the internal constitutive gene (target gene × (loading gene (control)/internal constitutive gene)) (Zambrose et al, 2020). The fold change value was generated from the normalized value.…”
Section: Densitometry Analysismentioning
confidence: 99%
“…Previously, a study showed that the ABP57 overexpression had increased the resistance of transgenic rice to drought stress (23). Moreover, the 35S::ABP57 transgenic Arabidopsis possessed root elongation changes and also restoration of root cells under drought and submergence conditions (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%